Asean: Handling Disruptions and Combating Corruption - , Haryono Umar (International Conference of ASEAN Prespective and Policy (ICAP); Vol 1 No 1 (2018): INTERNATIONAL CONFERENCE OF ASEAN PERSPECTIVE AND POLICY (ICAP), 2018)
This paper discusses the resilience of ASEAN member countries facing some obstacles to achieve common success. Various multilateral cooperation in the economic, political, legal, and others were implemented for achieving the goals. The revolution of industrial 4.0 which is characterized by super computers and robotics is just arrived. The implementation of industry 4.0has caused a disruption era as one of the exponential growth as elements. This disruption era became a night mare to the parties who are not able to transform and adapt to the change. The challenges facing ASEAN are not just technology, but also Trans national crime and Transorganized crime (TNC and TOC) such as corruption and money laundering. ASEAN member countries have agreed to face the disruption era and industry 4.0 by promoting the manufacturing sector as a superior product. Meanwhile, related to the prevention and eradication of corruption, ASEAN member countries agreed to prepare a mutual legal assistance (MLA). The importance of MLA because of the increasing sophistication of crime TNC and TOC but indeed there are difference legal practices among the ASEAN countries. There have been many forms of cooperation carried out both with regard to extradition, sharing information and knowledge, as well as litigation support.